2021
DOI: 10.18699/vj21.081
|View full text |Cite
|
Sign up to set email alerts
|

A prebreeding study of introgression spring bread wheat lines carrying combinations of stem rust resistance genes, Sr22+Sr25 and Sr35+Sr25

Abstract: The Sr22, Sr35, and Sr25 genes attract the attention of bread wheat breeders with their effectiveness against Puccinia graminis f. sp. tritici race Ug99 and its biotypes. The effectiveness and impact of Sr22+Sr25 and Sr35+Sr25 gene combinations on agronomic traits have not yet been studied. In the present article, these traits were studied using the spring bread wheat lines L503/W3534//L503, L503/Sr35//L503/3/L503 carrying the Sr22+Sr25 and Sr35+Sr25 genes during 2016–2020. These lines were assessed for resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similar results were obtained when identifying the effect of Sr22+Sr25 and Sr22+Sr35 gene combinations on lines of spring bread wheat compared to the L503 and Favorit cultivars. The grain yield of these cultivars and lines was 2.3-2.7 times higher in 2020 compared to 2019 (Sibikeev et al, 2021). Nevertheless, the analysis of grain productivity separately by years revealed that, in the C68Lr29 analogue lines, for all three years of study, the grain yield was significantly lower than that of the recipient cultivar C68.…”
Section: Effect Of the 7dl-7ae#1l•7ae#1s Translocation On Grain Produ...mentioning
confidence: 86%
“…Similar results were obtained when identifying the effect of Sr22+Sr25 and Sr22+Sr35 gene combinations on lines of spring bread wheat compared to the L503 and Favorit cultivars. The grain yield of these cultivars and lines was 2.3-2.7 times higher in 2020 compared to 2019 (Sibikeev et al, 2021). Nevertheless, the analysis of grain productivity separately by years revealed that, in the C68Lr29 analogue lines, for all three years of study, the grain yield was significantly lower than that of the recipient cultivar C68.…”
Section: Effect Of the 7dl-7ae#1l•7ae#1s Translocation On Grain Produ...mentioning
confidence: 86%
“…Sr25, linked to Lr19, was transferred to bread wheat in a translocated segment from Lophopyrum ponticum, which was also mapped to chromosome 7AL. It has been extensively deployed in many spring bread wheat cultivars of the Middle and Lower Volga regions of Russia [58], with some presence in the CIMMYT bread wheat germplasm. When introgressed into durum wheat, this gene provides good levels of resistance to the Spanish races (as indicated in the present study) as well as to the Ethiopian durum races.…”
Section: Discussionmentioning
confidence: 99%
“…The combination was found to be the most effective against the current Spanish races of stem rust, with reactions generally close to an immune response in the present study. Its use in spring bread wheat breeding programs in Russia was found to be associated with a higher ratio of dough tenacity to extensibility, lower flour strength, porosity, and bread volume [58]. In CIMMYT durum wheat backgrounds, the first generation of lines carrying both genes was characterized by severe yield and drought tolerance penalties; however, after two cycles of crossing/selection, the last generation of such lines has compensated for much of the yield or drought tolerance penalties, making them useful improved parents to use in any breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…For species from the secondary and tertiary gene pools, the genomic composition of which differs from the A, B, and D genomes of common wheat, the published data on their quality traits are scarce, and most of them are devoted mainly to investigating the allelic diversity of storage proteins and their possible impact on improving quality indicators [34][35][36]. Increased content of wet gluten and protein in the grain has been found in the hybrid lines containing alien chromatin from species of Timopheevi group (T. timopheevii, T. araraticum, genomes A t A t GG), Aegilops speltoides (genome S), wheatgrass Thynopyrum intermedium (genomes EEE st E st S t S t ) [24,[37][38][39][40], which makes it possible to assume that the introgression fragments carried over from wheat relatives may contain the genetic factors affecting the GC.…”
Section: Of 15mentioning
confidence: 99%